Assessment of a compaction indicator for oscillation rollers with a lumped parameter model. Issue 4 (10th August 2020) - Paulmichl, Ivan; Adam, Christoph; Adam, Dietmar; Völkel, Werner
Abstract : The stick–slip motion of the drum of four different oscillation rollers during near-surface compaction of non-cohesive soils was studied based on a lumped parameter model of the interacting oscillation roller–subsoil system. The aim of the study was to assess a novel compaction indicator for continuous compaction control with oscillation rollers, which was empirically found on the basis of field tests with a specific roller. In a comprehensive sensitivity study, the excitation frequency, the coefficient of friction at the contact between the drum and subsoil and the properties of the suspension between drum and frame were varied in order to demonstrate their impact on the drum response and thus on the compaction indicator. The results of this study essentially confirm the compaction indicator for the considered oscillation rollers for a wide range of soil stiffness. The found application limits of this value are clearly influenced by the device parameters and the operating oscillation frequency.